Fatigue life prediction of cylinder head for two stroke engine using constant and variable amplitude loading - Mohd Khairul Zaman, Muhamad Zin (2008)
Prediction of fatigue life on cylinder head for two stroke engine using constant and variable amplitude loading are presented. The objectives of this project are to predict fatigue life of cylinder head for two stroke internal combustion engine, to identify the critical location, to investigate the effect of mean stress of stress life and strain life method, to optimize the component material and to compare both constant and variable amplitude loading results. The structural and finite element modelling has been performed using a computer aided design and finite element analysis software package. The finite element model of component then analyzed using the linear elastic approach. Finally, the stress-strain state of component obtained previously will employ as input for the fatigue life. The effect of mean stress and materials optimize will be investigated. The cylinder head is the crucial part of the internal combustion engine. The failure of cylinder head can result in devastating damage to the engine including all the components from a tiny screw till a huge engine block. Life of cylinder head needs to be improved to prevent from any unpleasant problems. The result of the analysis was showed that there are no serious failure occurs at the part of the cylinder head and however it is observed that the minimum predicted life at the critical location is 102.38e-7 under constant amplitude loading and variable amplitude loading for stress life approach and the predicted life for strain life approach is 102.62 and 102.14 each under constant and variable amplitude loading. The optimization results were showed that 7075-T6 is the most superior material among the others.